PENGUKURAN KINERJA KEUANGAN PERUSAHAAN YANG MELAKUKAN AKUISISI - Kurniawan, Herwin (E-Journal Widya Ekonomika, 2020)
Acquisitions can be used to expand business and help companies avoid bankruptcy, with the aim is to accelerate the increase in assets and market dominance so that the company continues to grow and develop properly. not. This study aims to analyze the differences in financial performance of acquirer before and after acquiring will be better or vice versa. Company performance is measured using financial ratios of Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turn Over (TATO), Return On Equity (ROE), Operating Profit Margin (OPM). The method used in this research is descriptive research method. The data source used in this study is the financial report of PT XL Axiata, Tbk from 2010 to 2017 and analyzed using non parametric statistics used to analyze data. Paired Sample T-test is used to answer the hypothesis. The results of this study indicate that of the faiv financial ratios there are three ratios that have decreased after acquisition, namely the Total Asset Turn Over (TATO), Return On Equity (ROE), and Operating Profit Margin (OPM) and from the results of this calculation can also be seen that there is two financial ratio that has increased although not significant, namely: Current Ratio (CR) and Debt to Equity Ratio (DER).